Repensar la práctica docente en una nueva ecología del aprendizaje - Frías Butrón, Cinthia (2014)
This article is about the learning ecology, avision that identifies learning as a dynamicprocess, in continuous evolution, that iscarried out in an environment whereinteractions are explored in order togive comfort to the people involved, andexclusively guided to grow and learn.